Effect of Work Discipline, Compensation, and Motivation on Employee Performance at PT. Main Creation Synthesis - Nabila, Tasya Shafa; Krisnandi, Herry; Digdowiseiso, Kumba (Ridwan Institute, 2024)
This study aims to investigate the impact of Work Discipline, Compensation, and Motivation on Employee Performance at PT. Main Creation Synthesis, particularly focusing on whether these factors contribute to meeting performance targets. Primary data was collected through a questionnaire distributed to 127 respondents. The data analysis employed inferential analysis using multiple linear regression. The findings of the multiple linear regression analysis revealed that Work Discipline (X1) exhibits a positive and significant impact on employee performance. Similarly, the Compensation variable (X2) positively and significantly influences employee performance, as does Motivation (X3). These results suggest that improvements in work discipline, compensation, and motivation can enhance the performance of employees at PT. Main Creation Synthesis. The implications of this study emphasize the potential for employees at PT. Main Creation Synthesis to enhance their performance by fostering a strong work discipline, providing fair compensation, and promoting motivational factors. The study underscores the importance of addressing these aspects to contribute positively to overall employee performance and, consequently, achieving organizational targets.